2004
DOI: 10.1158/1078-0432.ccr-03-0689
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Microscopic Analysis of the Interaction between Cisplatin and the Copper Transporter ATP7B in Human Ovarian Carcinoma Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 35 publications
7
75
0
Order By: Relevance
“…Recent studies suggest that one mechanism by which CDDP is exported from the cell is via sequestration into vesicles of the secretory pathway (9). Because exosomes represent one of the outputs of this pathway, it was of interest to determine whether exosomes released by the CDDP-resistant cells contain more CDDP than those from the sensitive cells following loading of the cells with CDDP.…”
Section: Pt Content Of Exosomes Released From Cddpsensitive and Cddp-mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that one mechanism by which CDDP is exported from the cell is via sequestration into vesicles of the secretory pathway (9). Because exosomes represent one of the outputs of this pathway, it was of interest to determine whether exosomes released by the CDDP-resistant cells contain more CDDP than those from the sensitive cells following loading of the cells with CDDP.…”
Section: Pt Content Of Exosomes Released From Cddpsensitive and Cddp-mentioning
confidence: 99%
“…Studies of the cellular pharmacology of CDDP in cells overexpressing ATP7A and ATP7B indicate that CDDP is sequestered into vesicles belonging to the secretory pathway as well as lysosomes (7,8). Microscopic analyses with a fluoresceinconjugated CDDP have confirmed that CDDP accumulates in vesicles that contain ATP7A or ATP7B (9,10). Additional confocal microscopic analysis of fluorescein-conjugated CDDP in cells treated with drugs that inhibit trafficking pathways suggests that the accumulation of CDDP in the secretory compartment may require lysosomal function (10).…”
Section: Introductionmentioning
confidence: 99%
“…ATP7A and ATP7B are homologous Cu-transporting ATPases positioned in the trans-Golgi network. CisPt has been shown to trigger re-localization of these multi-domain, membraneassociated proteins towards more peripheral parts of the cell where they are thought to mediate CisPt resistance by sequestering the drug into intra-cellular vesicles [6][7]. The ATP7A/B proteins have been found to be over-expressed in CisPt resistant cancer cells [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental data suggest that one of mechanisms by which CDDP is exported from the cells is via sequestration into vesicules of the secretory pathway [14,23]. In this context it was of interest to compare LTR-stained vesicules accumulated in-and released by the parental cells following the drug treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidence indicates that CDDP is sequestered into intracellular vesicles, some of which belong to secretory pathways [10,14,23]. Therefore, we determined the efflux of the LTR dye following a single and/or combined effect of the drugs.…”
Section: Discussionmentioning
confidence: 99%